Estimation of norm of the annual runoff of the Tobyl rivers basin within the limits of the republic Kazakhstan territory at absence of the data supervision. (Journal of Geography and Environmental Management, 2016)
In the article spatial laws of distribution of annual runoff in the Tobyl River Basin are considered. Specification of calculation procedure of the annual runoff is made.